The EU directive on fixed-term contracts at company level - effects and influences in Denmark. A summary of the main conclusions of a report to the Danish local government and the association of local government employees' organisations - Larsen, Trine (Koebenhavn, 2008)
"This report examines the effects and influences of the EU's directive on fixedterm contracts in the Danish local government sector. The study is based on interviews with 259 workplaces, central management and trade union representatives from 14 randomly selected Danish municipalities. The report argues that although social partners at local level have transposed the directive, its actual effects are limited, as employers' recruitment strategies and fixed-term workers' working conditions have changed relatively little as a result of the directive. However, the directive has been more influential among municipalities, which have transposed the directive through local implementation initiatives and have more centralised procedures for regulating wage- and working conditions, particularly if the individual workplaces have no trade union representative."